COMPARISON OF EFFICACY OF PHENYTOIN AND LEVETIRACETAM FOR PREVENTION OF EARLY POST TRAUMATIC SEIZURES - Khan, Shahbaz Ali; Bhatti, Sajid Nazir; Alam, Aftab; Afridi, Ehtisham Ahmed Khan; Muhammad, Gul; Zadran, Khalid Khan; Alam, Sudhair; Aurangzeb, Ahsan (Journal of Ayub Medical College Abbottabad, 2016)
Background: The incidence of early post-traumatic seizures after civilian traumatic brain injury ranges 4-25%. The control of early post-traumatic seizure is mandatory because these acute insults may add secondary damage to the already damaged brain with poor outcome. Prophylactic use of anti-epileptic drugs have been found to be have variable efficacy against early post-traumatic seizures. The objective of this study was to compare the efficacy of Phenytion and Levetiracetam in prevention of early post-traumatic seizures in moderate to severe traumatic brain injury. Methods: This Randomized Controlled Trial was conducted in department of Neurosurgery, Ayub Medical College, Abbottabad from March, 2012 to March 2014. The patients with moderate to severe head injury were randomly allocated in two groups. Patients in group A were given phenytoin and patients in group B were given Levetiracetam. Patients were followed for one week to detect efficacy of drug in terms of early post traumatic seizures. Results: The 154 patients included in the study were equally divided into two groups. Out of 154 patients 115 (74.7%) were male while 29 (25.3%) were females. Age of patients ranges from 7-48 (24.15±9.56) years. Ninety one (59.1%) patients had moderate head injury while 63 (40.9%) patients had severe head injury. Phenytoin was effective in preventing early post traumatic seizures in 73 (94.8%) patients whereas Levetiracetam effectively controlled seizures in 70 (90.95%) cases (p-value of .348). Conclusion: There is no statistically significant difference in the efficacy of Phenytoin and Levetiracetam in prophylaxis of early post-traumatic seizures in cases of moderate to severe traumatic brain injury. Keywords: Phenytoin; Levetiracetam; Seizures; Post-traumatic; Epilepsy; Trauma; Head injury